Pengaruh Fungsi Sekretaris Dalam Meningkatkan Efektivitas Kinerja Pada Kantor Kecamatan Manggala Kota Makassar - Azwar Wijaya Syam; Irham Irham (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
This research is a quantitative descriptive study at the Manggala District office, Makassar City which aims to determine: (1) To determine the effect of the secretarial function in increasing work effectiveness at the Manggala District office, Makassar City (2) the supporting and inhibiting factors in the implementation of secretarial duties. in improving work effectiveness at the Manggala District office, Makassar City. The population as well as the research sample are all 23 employees of the Manggala District office, Makassar City. Data collection is taken by means of observation, questionnaires, interviews and documentation. The data analysis used is descriptive statistical analysis, namely percentages and quantitative methods with simple linear regression analysis using the help of SPSS version 25. The results show that: The value of the regression coefficient of performance effectiveness (X) on the secretarial function (Y) is 1,000 (100%), this indicates that the quality of performance effectiveness (X) has an influence on the accountability of the secretary function (Y) which is 100%, meaning that if there is a performance effectiveness (X) of 100%, it will increase the function of the secretary (Y) by 100%, and vice versa 2.a. Factors supporting the implementation of the secretarial function in increasing work effectiveness are: a) good coordination with all work units, and b) awareness of employees to increase cooperation. b. The inhibiting factor for the implementation of the secretarial function in increasing work effectiveness at the Manggala District office, Makassar City, is the absence of official vehicles